Complex Oxides under Simulated Electric Field: Determinants of Defect Polarization in ABO3 Perovskites. Issue 4 (10th December 2021) - Chi, Yen‐Ting; Van Vliet, Krystyn J.; Youssef, Mostafa; Yildiz, Bilge
Abstract: Polarization of ionic and electronic defects in response to high electric fields plays an essential role in determining properties of materials in applications such as memristive devices. However, isolating the polarization response of individual defects has been challenging for both models and measurements. Here the authors quantify the nonlinear dielectric response of neutral oxygen vacancies, comprised of strongly localized electrons at an oxygen vacancy site, in perovskite oxides of the form AB O3 . Their approach implements a computationally efficient local Hubbard U correction in density functional theory simulations. These calculations indicate that the electric dipole moment of this defect is correlated positively with the lattice volume, which they varied by elastic strain and by A‐site cation species. In addition, the dipole of the neutral oxygen vacancy under electric field increases with increasing reducibility of the B‐site cation. The predicted relationship among point defect polarization, mechanical strain, and transition metal chemistry provides insights for the properties of memristive materials and devices under high electric fields. Abstract : A novel local Hubbard U method resolves challenges in simulating defected semi‐conducting oxides under electric field. This approach reveals that the oxygen vacancy dipole moment correlates positively with lattice volume and B‐site cation electronegativity. The predicted relationships among point defect polarization, mechanical strain, and transition metal chemistry provide insights for properties of memristive materials and devices under high electric fields.